The Genome of Microthlaspi erraticum (Brassicaceae) Provides Insights Into the Adaptation to Highly Calcareous Soils - Mishra, Bagdevi; Ploch, Sebastian; Runge, Fabian; Schmuker, Angelika; Xia, Xiaojuan; Gupta, Deepak K.; Sharma, Rahul; Thines, Marco (Frontiers in Plant Science, 2020)
Microthlaspi erraticum is widely distributed in temperate Eurasia, but restricted to Ca2+-rich habitats, predominantly on white Jurassic limestone, which is made up by calcium carbonate, with little other minerals. Thus, naturally occurring Microthlaspi erraticum individuals are confronted with a high concentration of Ca2+ ions while Mg2+ ion concentration is relatively low. As there is a competitive uptake between these two ions, adaptation to the soil condition can be expected. In this study, it was the aim to explore the genomic consequences of this adaptation by sequencing and analysing the genome of Microthlaspi erraticum. Its genome size is comparable with other diploid Brassicaceae, while more genes were predicted. Two Mg2+ transporters known to be expressed in roots were duplicated and one showed a significant degree of positive selection. It is speculated that this evolved due to the pressure to take up Mg2+ ions efficiently in the presence of an overwhelming amount of Ca2+ ions. Future studies on plants specialized on similar soils and affinity tests of the transporters are needed to provide unequivocal evidence for this hypothesis. If verified, the transporters found in this study might be useful for breeding Brassicaceae crops for higher yield on Ca2+-rich and Mg2+ -poor soils.